Understanding Tietze’s Syndrome: A Rare and Often Overlooked Cause of Anterior Chest Wall Pain - Dańda, Karol; Chludek, Aleksandra; Chobot, Barbara; Wachowska, Marta; Chmielowiec, Julia; Czyżewicz, Zuzanna; Dworak, Kinga; Trędota, Natalia; Posid, Dominika; Lewczuk, Michał (Quality in Sport, 2026)
Introduction: Tietze’s syndrome is a rare, non-purulent arthropathy, most commonly associated with pain, swelling and tenderness in the 2nd and 3rd sternocostal junctions. Since its first description in 1921 many theories regarding the etiology and pathophysiology have been put forth, with a number of case reports and literature reviews. There is still, however, little agreement on the mechanisms underlying TS and diagnosis and treatment of TS remains challenging to clinicians to this day. Aim: The purpose of this study is to review the existing scientific literature regarding the epidemiology, pathophysiology, clinical presentation, methods of diagnosing and managing Tietze’s syndrome. Particular focus is placed on describing a comprehensive differential diagnosis of chest wall pain and outlining evidence-based treatment methods of TS. Materials and methods: A comprehensive review of literature was conducted using the PubMed and Google Scholar databases. The following search phrases were used: „Tietze”, „Tietze’s Syndrome”, „costochondritis”, „Zespół Tietze’a”. References were also screened in each article for additional sources. Conclusions: Tietze’s syndrome is a benign, self-limiting cause of chest wall pain that typically responds to simple symptomatic treatment but remains diagnostically challenging. The absence of standardized diagnostic criteria and limited epidemiological data often result in diagnostic uncertainty and unnecessary investigations. Careful clinical assessment and appropriate follow-up are essential to ensure accurate diagnosis and effective management without overlooking alternative pathology. Increased clinician awareness and further clinical reporting are needed to reduce diagnostic delays and optimize care.